COMPARATIVE CHARACTERISTICS OF THE DIAGNOSTIC CAPABILITIES OF SDCT AND LDCT FOR COVID-19 AND COMMUNITY- ACQUIRED PNEUMONIA. - Rakhmonova GE; Khamidova MA (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Relevance The thoracic organs (TCO) are a key anatomical region, and dysfunction directly impacts vital functions and physical endurance. For military personnel, for whom high performance, stress resistance, and physical activity are essential professional qualities, chest diseases can not only significantly reduce overall functionality but also lead to temporary  or  even  permanent  loss  of  combat  effectiveness.  According  to  several domestic  and  international  studies,  pneumonia  of  various  etiologies,  pleurisy, bronchopulmonary infections, and the consequences of traumatic chest injuries occupy a significant place in the structure of morbidity among military personnel.